A risk-based, distributed sensor installation concept for high voltage grid monitoring - Levente Rácz (Elsevier, 2022)
This paper presents a novel installation protocol to build a reliable and economical line monitoring system on high voltage power lines. The proposed method is able to iteratively determine the required number of sensors and their installation location for a predefined level of risk. First, it requires a general analysis of the transmission line, which ends with a critical span analysis. Then the risk arising from the variability of weather parameters along the transmission line must be determined. Finally, it is necessary to consider what kind of problem the thermal overheating can cause at the conductor (sagging, annealing) and which additional stages can be used to reduce the risk factor to the permissible level. A case study was investigated with the data of a Central-European high voltage power line to present how the proposed method works. The results showed that there are power lines on which only distributed sensor installation concepts result in a safe and economical solution. Applying the proposed method, a comprehensive and robust sensor system can be implemented, which can be a solid basis for any dynamic line rating (DLR) system.